Numerical modelling of radiant energy extinction by water medium containing bubbles and particles of various natures; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Shefer O. V. Olga Vladimirovna (2017, 2017)
Title screen